2014
DOI: 10.1055/s-0033-1356418
|View full text |Cite
|
Sign up to set email alerts
|

Balloon Sacroplasty as a Palliative Pain Treatment in Patients with Metastasis-Induced Bone Destruction and Pathological Fractures

Abstract: Purpose: In the case of metastatic involvement of the sacrum with destruction and consecutive pathological fracture, intense disabling pain is one of the defining factors. The feasibility, safety and pain development with cement augmentation were to be investigated. Materials and Methods: CT-guided balloon sacroplasty was conducted in 10 patients with metastasis-induced bone destruction of the sacrum. After establishment of the entry point, a K-wire was first introduced as far as the central tumor lesion via … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 12 publications
1
4
0
1
Order By: Relevance
“…In the present study, PSP was found to be feasible and highly efficacious, and pain relief and functional improvement were early and adequate. After PSP, 90% of the patients experienced immediate and significant improvement of pain and mobility, similar to other previously published literature (9111214). Therefore, PSP is a minimally invasive procedure that may be useful for patients with painful sacral metastases involving multiple sacral vertebral bodies–particularly for those in poor general condition–and offers several advantages over conventional treatments.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In the present study, PSP was found to be feasible and highly efficacious, and pain relief and functional improvement were early and adequate. After PSP, 90% of the patients experienced immediate and significant improvement of pain and mobility, similar to other previously published literature (9111214). Therefore, PSP is a minimally invasive procedure that may be useful for patients with painful sacral metastases involving multiple sacral vertebral bodies–particularly for those in poor general condition–and offers several advantages over conventional treatments.…”
Section: Discussionsupporting
confidence: 89%
“…In recent years, image-guided PSP has emerged as a feasible and effective treatment for painful and disabling sacral metastases, and this technique aims to alleviate pain and regain mobility in a manner similar to PVP or percutaneous kyphoplasty (PKP) of the cervical and thoracolumbar spine. Several reports and small series have demonstrated this technique's efficacy in providing pain relief and bone stabilization, although the mechanism underlying its analgesic effect remains incompletely understood (9111214282930).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mit der Dual-Energy-Computertomografie kann durch die hohe Ödemsensitivität und gleichzeitige Frakturvisualizierung im CT-Schnittbild eine weitere Verbesserung der Treffsicherheit erreicht werden, ohne dass die Strahlendosis im Vergleich zum Standard-CT weiter steigt [33,34]. Die CT kann auch hilfreich sein, wenn versucht wird, eine Fraktur von einer metastasierten Erkrankung zu unterscheiden, da sie bei einer Tumorbeteiligung eine kortikale Zerstörung und/oder eine Weichteilmasse zuverlässig darstellen kann [35,36].…”
Section: Bildgebungunclassified
“…[5][6][7][8] However, the few studies to date on the use of PSP for the treatment of painful sacral metastases have had small sample sizes and/or did not examine the use of PSP in combination with other therapies. [9][10][11][12] The aim of this retrospective study was to assess the safety and efficacy of PSP under fluoroscopy for the treatment of painful sacral metastases unresponsive to conservative treatments and to compare long-term outcomes after treatment with PSP alone versus PSP plus radiofrequency ablation (RFA).…”
mentioning
confidence: 99%